Hsp74/14‐3‐3σ Complex Mediates Centrosome Amplification by High Glucose, Insulin, and Palmitic Acid. Issue 7 (14th March 2019) - Lu, Yu Cheng; Wang, Pu; Wu, Qi Gui; Zhang, Rui Kai; Kong, Alice; Li, Yuan Fei; Lee, Shao Chin
Abstract: It has been reported recently that type 2 diabetes promotes centrosome amplification via 14‐3‐3σ/ROCK1 complex. In the present study, 14‐3‐3σ interacting proteins are characterized and their roles in the centrosome amplification by high glucose, insulin, and palmitic acid are investigated. Co‐immunoprecipitation in combination with MS analysis identified 134 proteins that interact with 14‐3‐3σ, which include heat shock 70 kDa protein 4 (Hsp74). Gene ontology analyses reveal that many of them are enriched in binding activity. Kyoto Encyclopedia of Genes and Genomes analysis shows that the top three enriched pathways are ribosome, carbon metabolism, and biosynthesis of amino acids. Molecular and functional investigations show that the high glucose, insulin, and palmitic acid increase the expression and binding of 14‐3‐3σ and Hsp74 as well as centrosome amplification, all of which are inhibited by knockdown of 14‐3‐3σ or Hsp74. Moreover, molecular docking analysis shows that the interaction between the 14‐3‐3σ and the Hsp74 is mainly through hydrophobic contacts and a lesser degree ionic interactions and hydrogen bond by different amino acids residues. In conclusion, the results suggest that the experimental treatment triggers centrosome amplification via upregulations of expression and binding of 14‐3‐3σ and Hsp74.